on the other side - Lidin, Konstantin (project baikal, 2019)
The history of architecture “on the other side of the curtain” is also far from unambiguity. One of the most significant figures of the American school in the 20th century is Louis Kahn. Architectural historians debate about him and his ideas in an open and emotional dialogue. The parallels concerning the attitude towards the heritage of the 20th century are far from being optimistic “on both sides”. A. Palagina expresses her worries about destruction of masterpieces of Metabolism in Japan.
Keywords: history of architecture; Louis Kahn; heritage of the 20th century